Placebos as a Source of Agency: Evidence and Implications - Friesen, Phoebe (Frontiers in Psychiatry, 2019)
Bioethical discussions surrounding the use of placebos in clinical practice have long revolved the conflict between beneficence and autonomy that arises when doctors lie to their patients in order to bring about a clinical benefit. While these discussions have been insightful and productive, they reinforce the notion that placebo effects are only brought about through deception. This paper challenges this notion, looking beyond the paradigmatic clinical encounter involving deceptive placebos, and towards the many other routes that bring about placebo effects. After briefly describing the bioethical terrain surrounding the deceptive use of placebos in clinical practice, section one offers an examination of the various ways that placebo effects are brought about. These include descriptions of how placebo responses are produced by classical conditioning, expectations, affective pathways, open label placebo treatments, and additional factors that do not fall easily into a single category. The following section takes up each of these routes that produce placebo responses and examines how each can be harnessed to bring about clinical benefits without the use of deception. This provides grounding for reconceiving of the placebo effect as a clinical tool that is not always in conflict with patient autonomy and can even be seen as a source of agency. In the final section, implications of the shift away from seeing placebos as necessary deceptive are discussed. These include a discussion of how recognizing the many routes by which placebo effects are produced leads us to look beyond the clinical encounter and mainstream medicine as the primary sites of placebo responses, how important acknowledging the limits of placebo effects will be when we do so, as well as the difficulties of disentangling agency, responsibility, and blame within medicine.